Comparison of T1-S1 Spine Height of Postoperative Rib-based Implant Patients With Age-matched Peers. Issue 7 (August 2020) - Johnson, Mitchell A.; Cahill, Patrick J.; Qiu, Catherine; Lott, Carina; Mayer, Oscar H.; Flynn, John M.; Anari, Jason B.
Abstract : Background: Severe early-onset scoliosis leads to deficient spine height, thoracic growth inhibition, and ultimately pulmonary compromise. Rib-based growing instrumentation seeks to correct thoracic deformities, in part by correcting the spinal deformity, adding height, increasing thoracic volume, and allowing for continual spinal growth until maturity. However, the amount of growth in these patients relative to their peers is unknown. Methods: Sixty patients who had undergone surgical intervention for the treatment of early-onset scoliosis were assessed via radiographic measurements of coronal T1-S1 height and major curve angle before implantation and again at most recent follow-up (minimum 2 years). T1-S1 measurements were then compared with age-matched peers to assess growth differences. Clinical information was examined for relevant parameters. Results: The average age of our cohort at initial surgery and most recent follow-up was 4.4±3.8 and 10.0±4.4 years old, respectively. In this patient set, there was an average increase in T1-S1 height of 13.1±11.1 mm per year, with the majority of growth occurring in the first 2 years following implantation, and improvement in a major curve from 68±8 to 53±7 degrees. Overall, 77% of patients saw improvement in the major curve at most recent follow-up. Furthermore, a statistically significant greater percent of expected growth was seen in congenital compared with neuromuscular scoliosis ( P <0.001). In addition, a weak negative correlation was observed between a number of surgical lengthenings and T1-S1 growth. Conclusions: Rib-based implant intervention has been shown to improve the major curve, but only improves growth potential to around 80% of expected growth. Scoliosis diagnosis type also influences growth rate potential, with congenital scoliosis patients being surgically treated earlier in life and having a growth rate approaching that of a healthy individual. Level of Evidence: Level III—Case control.